Minimally expanded breast cancer tumor-infiltrating-lymphocytes provide guidance for therapeutic selection - Aran, Andrea; Lázaro, Gonzalo; Marco, Vicente; Peg, Vicente; Faus, Maitane; Garrigós, Laia; Pérez-García, José; Cortés, Javier; Martí, Mercè (Frontiers in Immunology, 2025)
IntroductionThe analysis of tumor-infiltrating lymphocytes often requires techniques that expand their numbers, potentially introducing bias. To address this, we performed a detailed analysis of minimally cultured TILs to evaluate whether this approach better preserves their characteristics.MethodsThe TIL culture method was based solely on tumor tissue with low IL-2 supplementation to minimize artificial alterations. The validity of this approach was confirmed by the correlation between CD3+ T cell percentages in cultures and infiltration patterns observed by immunohistochemistry. Immunophenotyping, cytokine release, and TCR repertoire analysis were used to characterize CD4+ and CD8+ T cell subsets and their molecular features during minimal expansions.ResultsHigh TIL infiltration areas did not consistently correspond to an increased presence of any T cell subset; both CD4+ and CD8+ T cells frequently coexisted in these regions. In contrast, low TIL infiltration sections often displayed a higher proportion of CD4+ T cells. An inverse correlation between CD4+ T cell percentages and cytotoxic molecules was observed, indicating reduced cytotoxic activity in low-TIL sections with abundant CD4+ T cells. TCR repertoire analysis revealed differences between T cell subsets: CD4+ T cells were associated with longer TRA CDR3 nt and shorter TRB N(D)N nt lengths, along with lower diversity, while CD8+ T cells did not exhibit significant correlation with any TCR feature.DiscussionThis study highlights the distinct biological features of CD4⁺ and CD8⁺ TIL populations within the tumor microenvironment that can be preserved using a minimally expanded TIL approach. The observed associations between IHC patterns, T cell subset composition, cytotoxic potential, and TCR repertoire diversity help identify which biopsy regions yield TILs with greater therapeutic potential, thus providing guidance for TIL selection in immunotherapy.